Trestní právo Evropské unie – vývoj, specifika a další směřování - Petr Zarivnij (Časopis pro Právní Vědu a Praxi, 2016)
The creation of economically integrated Europe based on free movement across borders has also stimulated an increase in transnational crime. Events that everyday happen in the world bring a number of changes that may have impact on the area of freedom, security and justice in the European Union. Terrorism, cybercrime and certain forms of radicalization, events such as the bombings in Madrid, London and New York have always had an impact on the revision of the EU agenda in the field of security. New problems are emerging on a daily basis and require striking a balance between the legitimate requirements of public order, national security and immigration controls on the one hand, and protection of human rights and freedoms on the other. Finding the right, or suitable solution can be tricky, especially when taken into account that these problems have “European dimension”. Criminal law always confirmed that the expansion of the influence of European law has its limits. However the area of criminal law cannot be completely immune to the influence of European standards. The question is not so much whether the national criminal law of the Member States can resist, but rather which specific areas within national criminal law will be next, and especially when it will happen. The EU is quite specific environment. And as such, it has to deal with specific problems. For example, free movement of persons also means increased mobility of serious crimes. Nevertheless, one of the most important objectives of the EU is to ensure the protection and safety of its citizens. For this reason, the EU must develop legal tools that enable and streamline the prosecution and punishment of offenders who commit cross-border crime. In recent years the area of European criminal law is considered to be one of the fastest growing in the Union. On the other hand, this development is quite noticeable in relation with the question of sovereignty of the individual Member States. And that could be seen as one of the obstacles that European criminal law has to deal with. The structure of the criminal justice system at European level is inspired by the model of national penal systems, which can be explained simply by the fact that the EU as such was developed based on the legal traditions of its members. However, it is not a “one-way” process because some of the standards of national criminal law are affected by the European legislation. The fact that there is globalization (or Europeanization) of criminal activities, is a reason enough for closer police and judicial cooperation within the EU. Development related to the field of European criminal law was influenced by the Maastricht, Amsterdam, Nice and Lisbon Treaties, as well as accompanying programmes of Tampere, The Hague and Stockholm. The development has experienced instruments enhancing judicial and police cooperation, the harmonization of substantive and procedural criminal law etc. Most recently, the EU targets in the area of criminal law are laid down in the Post-Stockholm programme, for which, however, it is not yet clear whether it is a product of realism or just lack of ambition. That is because the Post-Stockholm programme is designed quite generally. On the other hand, the main areas of interest are likely to be further specified.